Integrated traditional Chinese and conventional medicine in treatment of severe community-acquired pneumonia: study protocol for a randomized placebo-controlled trial - Haifeng Wang; Jiansheng Li; Xueqing Yu; Su-yun Li (Trials, 2018)
Abstract Background Community-acquired pneumonia, especially severe community-acquired pneumonia (SCAP), remains the leading cause of death in the world. Despite advances in antimicrobial therapy, the mortality rates due to SCAP have not decreased significantly since antibiotics became routinely available. Traditional Chinese medicine (TCM) has been used for treating pneumonia for thousands of years. It is popular and widely practiced in Asia. In recent decades, evidence from both clinicians and patients suggests that TCM has some beneficial effect on SCAP. Thus, this study aims to compare the efficacy of a combination of a conventional drug and TCM to the conventional drug alone, to provide a scientific basis for clinical decisions. Methods/design A prospective, multi-center, single-blinded, double-dummy, and randomized controlled clinical trial is being conducted to test the therapeutic effects of a combination of conventional medicine and TCM versus conventional medicine in the treatment of SCAP. A total of 198 patients will be enrolled in this study, with 99 in each treatment group (combination group or conventional medicine group). The TCM will be administered twice daily for 28 days. All patients will be followed for 3 months. The primary outcome measure is treatment failure, which is defined as clinical deterioration. Secondary outcome measures are time to clinical stability, length of hospital stay, in-hospital mortality, SOFA questionnaire, quality of life and cost of treatment. Discussion It is hypothesized that the combination of a conventional drug and TCM will reduce treatment failure, time to clinical stability, length hospital of stays, and in-hospital mortality, and improve the quality of life of SCAP patients. Trial registration ClinicalTrials.gov, NCT03185923. Registered on 20 June 2017.